2013
DOI: 10.21608/ejarc.2013.214246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Growth Regulators Under Different Planting Dates on Growth and Yield of Cotton

Abstract: This study was carried out at the Experiment and Research Station, Faculty of Agriculture, Cairo University, Giza in two growing seasons (2010 and 2011) to study the effect of three sowing dates; (25 March, 25 April, and 25 May) and some growth regulators i.e.,(Indole acetic acid (IAA) at the rates of 50, 100 and I50 ppm, Naphthalene acetic acid (NAA) at the rates of 10, 20 and 30 ppm and Mepiquate chloried (Pix) 50, 100 and I50 ppm) on Egyptian cotton cultivar (Giza 92). A split-plot design with three repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…It is difficult to raise organic matter beyond 4.5%. Biovita (sea weed) is a rich source of organic matter that has significant impact on yield components and seed cotton yield but has not much significant impact on quality of cotton i.e., GOT%, staple length, fineness and fiber strength (Elayan, 2008;Abdallah and Mohamed, 2013). Studies suggested that application of farm yard manure improves fiber yield by way of improved GOT (Desouza et al, 2023).…”
Section: Saeed Ahmadmentioning
confidence: 99%
“…It is difficult to raise organic matter beyond 4.5%. Biovita (sea weed) is a rich source of organic matter that has significant impact on yield components and seed cotton yield but has not much significant impact on quality of cotton i.e., GOT%, staple length, fineness and fiber strength (Elayan, 2008;Abdallah and Mohamed, 2013). Studies suggested that application of farm yard manure improves fiber yield by way of improved GOT (Desouza et al, 2023).…”
Section: Saeed Ahmadmentioning
confidence: 99%